Construction and performance of OLED devices prepared from liquid-crystalline TADF materials. Issue 36 (8th September 2022) - Suleymanova, Alfiya F.; Shafikov, Marsel Z.; Chen, Xinrui; Wang, Yafei; Czerwieniec, Rafal; Bruce, Duncan W.
Abstract : Emissive liquid-crystalline phthalonitrile carbazole conjugates showing low roll-off in OLED devices. Abstract : The device performance is reported for three compounds which show both thermally activated delayed fluorescence and liquid crystallinity, and use the donor 3, 6-bis(3, 4-didodecyloxyphenyl)carbazole. Two of the compounds, whose photophysics were reported previously, are based on a terephthalonitrile acceptor. A third and new compound is based on an isophthalonitrile acceptor and shows a more temperature-accessible mesophase and enhanced solution emission quantum yield. Two of the compounds show device external quantum efficiencies of between 2–3% and exhibit very small efficiency roll off. The responses are evaluated in terms of the specific nature of the materials.